1990
DOI: 10.1128/jb.172.12.6759-6763.1990
|View full text |Cite
|
Sign up to set email alerts
|

Deletion analysis of the 51-kilodalton protein of the Bacillus sphaericus 2362 binary mosquitocidal toxin: construction of derivatives equivalent to the larva-processed toxin

Abstract: Bacillus sphaericus 2362 produces a binary toxin consisting of 51-and 42-kDa proteins, both of which are required for toxicity to mosquito larvae. Upon ingestion by larvae, these proteins are processed to 43 and 39 kDa, respectively. Using site-directed mutagenesis, we have obtained N-and C-terminal deletions of the 51-kDa protein and expressed them in B. subtilis by using the subtilisin promoter. Removal of 21 amino acids from the N terminus and 53 amino acids from the C terminus resulted in a protein with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…16 KK 17 3 AA (51N1) and 16 KKF 18 3 AAA (51N2) did not affect the biological activity. This reconfirms the earlier observation on the nonessentiality of this region, as it is located upstream to the proteolytic cleavage sites of the 51-kDa peptide (8,10). Replacement of three amino acids in the N-terminal regions, 32 YNL 34 3 AAA (51N3) and 38 SKK 40 3 AAA (51N4) by alanine blocks resulted in total loss of biological activity.…”
Section: Mutations At the N-and C-terminal Regions Of The 51-kda Peptidesupporting
confidence: 89%
See 2 more Smart Citations
“…16 KK 17 3 AA (51N1) and 16 KKF 18 3 AAA (51N2) did not affect the biological activity. This reconfirms the earlier observation on the nonessentiality of this region, as it is located upstream to the proteolytic cleavage sites of the 51-kDa peptide (8,10). Replacement of three amino acids in the N-terminal regions, 32 YNL 34 3 AAA (51N3) and 38 SKK 40 3 AAA (51N4) by alanine blocks resulted in total loss of biological activity.…”
Section: Mutations At the N-and C-terminal Regions Of The 51-kda Peptidesupporting
confidence: 89%
“…Thus, either a direct disturbance of the loop structure (51N3) or ␣-helix (51N4) in this region may affect the gut (receptor) binding activity of the toxin. Earlier studies have shown that the deletion of 41 amino acids from the N-terminal region of the 51-kDa peptide of B. sphaericus 2362 destroyed its biological activity (8).…”
Section: Mutations At the N-and C-terminal Regions Of The 51-kda Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the LC50 against C. quinquefasciatus larvae produced by truncated BinB protein in this study is similar to that report of previous work (18), implying that this truncated form of BinB is effectively functional. The results showed that mutations at C67 and C161 (C67A, C67S, C161A, and C161S) rendered toxin inactive, while the mutants C241A and C241S showed comparable activity to that of the wild type (Table 1).…”
Section: C67 and C161 Are Required For Toxicity Of Binary Toxinsupporting
confidence: 79%
“…BinB wild type and mutants were constructed as truncated protein containing amino acids 33-408 and expressed in E. coli BL21(DE3)pLysS. This BinB derivative was previously shown to have molecular weight similar to processed BinB in the mosquito larvae gut that still retains maximum toxicity, thus considered as an active form of toxin (18). BinB wild type and variants (C67A, C67S, C161A, C161S, C241A, and C241S) were expressed as inclusion bodies at comparable levels, and SDS-PAGE analysis showed that the expressed proteins had molecular weight about 43 kDa as expected (Fig.…”
Section: Resultsmentioning
confidence: 99%